Resilience and social capital - Bernier, Quinn; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2014)
Increasingly, resilience is being incorporated into planning and social protection policy. People have been facing shocks, both natural and anthropogenic, forever, devising and innovating a variety of institutional responses to cope with, recover from, and prevent future impacts. Central to these shocks and this coping capacity, but often underexplored, is the role of social capital. This paper, using the case studies of iddirs (funeral societies) in Ethiopia and migrant networks in the Philippines, explores the contribution of local forms of social capital to building and strengthening the resilience of individuals and communities, focusing on their contributions to coping, adaptive, and transformative capacities. This paper argues that understanding clearly the role that existing social capital can play in building resilience is a necessary first step for policymakers. The authors suggest policy interventions to fill gaps where and when necessary while supporting and deepening existing social capital.